PENEGAKAN HUKUM TINDAK KEKERASAN TERHADAP ANAK (PASAL 80 AYAT 2 UNDANG-UNDANG NO. 35 TAHUN 2014) DI POLRES BOYOLALI - SUBIYATI, SUBIYATI (Dinamika Hukum, 2017)
The purposes of this research are to study and analyze the process of thelegal supremacy of the violence act against the children in Polres Boyolali, tostudy and analyze the efforts of Polres Boyolali in the process of acceleration inhandling the violence criminal act against the children in Polres Boyolali.The background of the research focus is the children protection whichcovers the focus on the violence act. It is a legal action which brings a legalconsequence, therefore, it needs a legal assurance for the activities of the childrenprotection and the legal certainty needs to be made for the sustainability of theactivities of children protection and prevent the abuses which bring negativeconsequences in the implementation of the legal supremacy.This research used a kind of juridical sociological research. The electedlocation is Polres Boyolali. The characteristic of this research is descriptive thataccording to Soerjono Soekamto is â€œa research which provides initial data ascarefully as possible about human, condition or other symptomsâ€. Object of theresearch is the legal supremacy of violence act against the children which hadbeen handled by Polres Boyolali. In this research, the writer used a qualitativemethod.The result of the research was that Polres Boyolali conducted the legalsupremacy which had been conducted in the violence protection against thechildren according to Article 30 paragraph 2 of UU RI No. 35 of 2014 that wasKapolres (Chief of Boyolali police) through Kasat Reskrim (Chief of CriminalReserves) issued an Order Letter of Arrest, Investigation after finding the suspectand then conducted arrest and detention against the Suspect which was accordingto the law, it could be taken the accountability. The efforts of Polres Boyolali inhandling the criminal act of cruelty against children was that the Investigatorconducted the steps of case file for the completeness to be submitted to theAttorney which was begun from the examination on the Witnesses, the CrimeScene, Reconstruction on the Suspect and the result of juridical analysis that theSuspectâ€™s action had met the element of Article 80 paragraph (1) of UU RI No. 35of 2014 regarding the Children Protection that is conducting violence against thechildren.Keywords: legal supremacy and children protection.